Complement Evasion by Pathogenic Leptospira - Fraga, Tatiana Rodrigues; Isaac, Lourdes; Barbosa, Angela Silva (Frontiers in Immunology, 2016)
Leptospirosis is a neglected infectious disease caused by spirochetes from the genus Leptospira. Pathogenic microorganisms, notably those who reach the blood circulation such as Leptospira, have evolved multiple strategies to escape the host complement system, which is important for innate and acquired immunity. Leptospira avoid complement-mediated killing through: (i) recruitment of host complement regulators; (ii) acquisition of host proteases that cleave complement proteins on the bacterial surface; and, (iii) secretion of proteases that inactivate complement proteins in the Leptospira surroundings. The recruitment of host soluble complement regulatory proteins includes the acquisition of Factor H (FH) and FH-like-1 (alternative pathway), C4b Binding Protein (C4BP) (classical and lectin pathways) and vitronectin (Vn) (terminal pathway). Once bound to the leptospiral surface, FH and C4BP retain co-factor activity of Factor I in the cleavage of C3b and C4b, respectively. Vn acquisition by leptospires may result in terminal pathway inhibition by blocking C9 polymerization. The second evasion mechanism lies in plasminogen binding to the leptospiral surface. In the presence of host activators, plasminogen is converted to enzymatically active plasmin, which is able to degrade C3b, C4b and C5 at the surface of the pathogen. A third strategy used by leptospires to escape from complement system is the active secretion of proteases. Pathogenic, but not saprophytic leptospires, are able to secrete metalloproteases that cleave C3 (central complement molecule), Factor B (alternative pathway), C4 and C2 (classical and lectin pathways). The purpose of this review is to fully explore these complement evasion mechanisms, which act together to favor Leptospira survival and multiplication in the host.